2023
DOI: 10.3390/su15075681
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence, Distribution, Damage Potential, and Farmers’ Perception on Fall Armyworm, Spodoptera frugiperda (J.E. Smith): Evidence from the Eastern Himalayan Region

Abstract: The fall armyworm (FAW), Spodoptera frugiperda (J.E. Smith), is a polyphagous non-native pest identified as a serious threat to crop production and food security globally, including in India. Its unintentional introduction and quick coverage in large areas is a serious concern to millions of farmers in the eastern Himalayan region. However, detailed understanding of farmers’ perceptions and the biological attributes associated with the meteorological factors for FAW is limited. The present investigation, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
1
1
0
Order By: Relevance
“…In this research we observed greater FAW damage to maize in early growth stages (the early-whorl, V3–V6), with both damage incidence and severity declining in maize plants in the late-whorl and reproductive stages. Similar results have been observed elsewhere in southern Asia 29 , 31 33 . However, little damage to reproductive tissues may have a greater impact on yield than the foliar damage in the early-whorl growth stages.…”
Section: Discussionsupporting
confidence: 91%
“…In this research we observed greater FAW damage to maize in early growth stages (the early-whorl, V3–V6), with both damage incidence and severity declining in maize plants in the late-whorl and reproductive stages. Similar results have been observed elsewhere in southern Asia 29 , 31 33 . However, little damage to reproductive tissues may have a greater impact on yield than the foliar damage in the early-whorl growth stages.…”
Section: Discussionsupporting
confidence: 91%
“…This counting method continued in a “W” fashion, gathering data from at least 40 plants. Additionally, they were advised to examine damaged whorls and record the number of larvae present in infested whorls at 15-day intervals 45 . Both expressed in mean egg mass/ plants and mean larvae/ plants, respectively.…”
Section: Methodsmentioning
confidence: 99%